Evaluation of The Pan-Immune-Inflammation Value in Patients with Chronic Rinosinusitis - Mehmet Emre Sivrice; Yusuf Tuncel; Hasan Yasan; Erdoğan Okur; Yusuf Çağdaş Kumbul; Vural Akın (The Turkish Journal of Ear Nose and Throat)
Objective: In this study, we aimed to investigate the pan-immune inflammation value (PIV) if it can predict the nasal polyp endotype of the patient without biopsy. In this regard, we aimed to obtain a new diagnostic tool that can guide the treatment of patients who do not accept biopsy or are not suitable for surgery due to their comorbidities. Material and Methods: The study was designed as a retrospective case–control study. The study group consisted of 198 patients in the CRS group and there were 396 patients in the control group. The age, gender, grade, CBC parameters and pan-immune-inflammation value were compared statistically between the groups. Results: A statistically significant difference was observed between the control and CRS groups in terms of the PIV parameter (p<0.001). In CRS endotyping, no significant difference was observed between the type 2 and non-type 2 groups in terms of the PIV parameter (p=0.276). Conclusion: According to our results, the PIV parameter was statistically significantly higher in CRS patients than in the control group. However, it was not useful for endotyping the disease and predicting recurrence. We believe that further studies testing different inflammatory indices will be beneficial for these purposes.